Physicochemical and sensory attributes of scones made from wheat–taro (Colocasia esculenta)–lentils (Lens culinaris) composite flour - Tengetile N. Shongwe; Solomon Worku Kidane; Jermiah S. Shelembe; Thabile P. Nkambule (Legume Science, 2024)
Abstract The effect of blend proportion on the functional properties of wheat–taro–lentil composite flour and the physicochemical and sensory quality of scones was studied. The water absorption capacity (WAC), oil absorption capacity (OAC) and bulk density (BD) significantly (p < .05) increased whereas the swelling index (SWI) decreased with increase in the proportion of lentil flour. Batter viscosity significantly (p < .05) decreased from 1972 to 1968 cP with increase in the proportion of lentil flour. The crude protein content increased from 5.81% to 9.83% and the ash content decreased from 4.61% to 2.29% with increase in the lentil proportion. Specific volume, volume and height decreased with increase in the proportion of lentil. The baking loss increased from 5.36% to 13.56% with increase in taro flour proportion. The L*, a* and b* colour values and sensory attributes were also significantly affected by the blend proportions. Based on the results, lentils can be incorporated up to 30% and taro up to 10% for a protein‐enhanced and acceptable product.